Research of Pattern Switching Strategy for Locomotive Automatic Train Operation System - Yonghui CAI; Penggang ZHANG; Qiao NING; Yexuan LIU; Shuangshuang SHANG (机车电传动)
Due to the limitation of railway basic equipment technology and domestic complex operating environment, locomotive automatic train operation still needs to work on duty. Therefore, there should be a perfect automatic driving system mode switching strategy to define the right of the on-duty personnel and the automatic driving. Based on the principle of locomotive operation safety and longitudinal dynamic analysis of train stability during dynamic switching, the mode switching strategy of locomotive autopilot system was expounded. The strategy had been applied to the practical application of locomotive automatic driving, and it was proved by a lot of practical cases that the automatic driving mode switching strategy of the locomotive could effectively ensure the safe and stable operation of the train during the switching of the locomotive control mode, and had a good running effect.